2023
DOI: 10.1111/opo.13126
|View full text |Cite
|
Sign up to set email alerts
|

Forward‐scattered and backward‐scattered light in moderate keratoconus

Abstract: Keratoconus (KC) is a progressive corneal stromal thinning disorder in which the cornea bulges outwards into a cone-like shape. 1,2 It is the most common primary corneal ectasia with a multifactorial aetiology, including genetic and environmental factors. 3 KC causes a myopic shift and irregular astigmatism, but its progression can also lead to thinning and protrusion. 4 These changes are caused by a disturbance of the fragile balance of well-distributed corneal extracellular matrix and cells. 5 In advanced ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…In one account, the average total corneal densitometry for individuals with Stage II/III keratoconus is reported as 18.8 ± 2.7 GSU. 16 An increase in corneal densitometry is expected following CXL, regardless of persistent haze development, with some studies demonstrating a return toward baseline within a year 3,17 and others suggesting that corneal densitometry may remain elevated above preoperative measurements despite full recovery of vision, which aligns with our findings. 18 Our case is also consistent with recent research, which indicates that the highest densitometry readings are found in the anterior 120 μm of the cornea and the inner concentric zone (0.0–2.0 mm) after CXL.…”
Section: Discussionsupporting
confidence: 89%
“…In one account, the average total corneal densitometry for individuals with Stage II/III keratoconus is reported as 18.8 ± 2.7 GSU. 16 An increase in corneal densitometry is expected following CXL, regardless of persistent haze development, with some studies demonstrating a return toward baseline within a year 3,17 and others suggesting that corneal densitometry may remain elevated above preoperative measurements despite full recovery of vision, which aligns with our findings. 18 Our case is also consistent with recent research, which indicates that the highest densitometry readings are found in the anterior 120 μm of the cornea and the inner concentric zone (0.0–2.0 mm) after CXL.…”
Section: Discussionsupporting
confidence: 89%